Controlled release of chitosan/heparin nanoparticle-delivered VEGF enhances regeneration of decellularized tissue-engineered scaffolds - Tan Q (Dove Medical Press, 2011)
Qi Tan, Hao Tang, Jianguo Hu, Yerong Hu, Xinmin Zhou, Yunming Tao, Zhongshi WuDepartment of Cardiothoracic Surgery Second Xiangya Hospital, Central South University, Changsha 410011, People's Republic of ChinaAbstract: Regeneration deficiency is one of the main obstacles limiting the effectiveness of tissue-engineered scaffolds. To develop scaffolds that are capable of accelerating regeneration, we created a heparin/chitosan nanoparticle-immobilized decellularized bovine jugular vein scaffold to increase the loading capacity and allow for controlled release of vascular endothelial growth factor (VEGF). The vascularization of the scaffold was evaluated in vitro and in vivo. The functional nanoparticles were prepared by physical self-assembly with a diameter of 67–132 nm, positive charge, and a zeta potential of ~30 mV and then the nanoparticles were successfully immobilized to the nanofibers of scaffolds by ethylcarbodiimide hydrochloride/hydroxysulfosuccinimide modification. The scaffolds immobilized with heparin/chitosan nanoparticles exhibited highly effective localization and sustained release of VEGF for several weeks in vitro. This modified scaffold significantly stimulated endothelial cells' proliferation in vitro. Importantly, utilization of heparin/chitosan nanoparticles to localize VEGF significantly increased fibroblast infiltration, extracellular matrix production, and accelerated vascularization in mouse subcutaneous implantation model in vivo. This study provided a novel and promising system for accelerated regeneration of tissue-engineering scaffolds.Keywords: nanoparticle, scaffolds, VEGF, control release, vascularization, regeneration